Porous hydrogen bond material for extracting uranium from seawater and preparation method thereof
By using porous hydrogen bonding materials in seawater for uranium extraction, the problem of difficulty in uranium extraction in seawater in the prior art has been solved, and efficient and stable uranium adsorption effect has been achieved.
Patent Information
- Application Number
- CN202411220810.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2025-02-28
AI Technical Summary
The prior art is difficult to effectively extract uranium from seawater, especially when the uranium concentration in seawater is extremely low and there are a large number of interfering ions, and the existing adsorption materials are amorphous polymers, resulting in unstable adsorption performance.
The cyano compound is heated and stirred in a solvent containing an inorganic base to form an amidoxime compound, and recrystallizes it by evaporation of the solvent to form a porous hydrogen bond material with regular pores.
Selective adsorption of uranium in seawater was achieved, with an adsorption amount of about 50 times that of V, and excellent adsorption performance was shown under the condition of real seawater pH=8, and the adsorption performance of the material remained above 90% after 5 cycles.
Smart Images

Figure CN119528763A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of extracting uranium from seawater, and in particular to a porous hydrogen-bonded material for extracting uranium from seawater and a preparation method thereof. Background Art
[0002] Environmental pollution and resource shortage are two major problems facing the world today. Nuclear energy, as a sustainable green energy with minimal impact on the environment, has received widespread attention and development from countries around the world. As an important nuclear fuel, most nuclear power plants in the world use uranium (VI). The ocean contains a large amount of low-concentration uranium, with a reserve of 4.5×1010 tons, which is about a thousand times the reserve of uranium (VI) from conventional sources such as terrestrial mines, which can ensure the long-term and stable development of nuclear power. In addition, seawater has strong mobility and no geographical restrictions, indicating that the strategy is feasible. This makes extracting uranium from seawater the top priority for mankind's future use of nuclear energy. Therefore, selective enrichment of U(VI) from seawater is of great significance to the development of nuclear energy and stable energy supply.
[0003] However, since uranium (VI) is present in very low concentrations in seawater and coexists with various interfering ions at higher concentrations, such as Na + , K + Mg 2+ , Ca 2+ Therefore, it is very difficult to selectively extract uranium ions from many ions; the pH and salinity in seawater also have an impact on the adsorption of uranium ions, so it is also difficult to extract uranium ions in a pH range close to that of seawater.
[0004] In order to solve the above technical problems, the prior art with DOI number 10.1002 / anie.201913644 proposes to prepare a black phosphorus-polyacrylamide oxime fiber with enhanced uranium extraction ability by synthesizing black phosphorus nanosheets into polyacrylamide oxime, so as to be applied to seawater uranium extraction through fiber synergistic photocatalytic effect. However, the adsorption of V by the black phosphorus-polyacrylamide oxime fiber of the prior art is stronger than that of U, and the adsorption amount is the largest at pH = 5, while the pH of real seawater is 8, which makes it difficult to effectively extract uranium from seawater. The prior art with DOI number 10.1002 / aenm.201802607 proposes a pre-amide oxidation strategy through a spinning process, and synthesizes a poly (imide dioxime) nanofiber adsorbent with a three-dimensional porous structure for extracting uranium from seawater, but the selectivity ratio of the adsorbent for U / V is about 1.4, which makes it difficult to achieve effective adsorption of uranium.
[0005] Based on the above, it can be known that the existing adsorption materials are difficult to effectively extract uranium directly from seawater, and the adsorption materials in the above two prior arts are amorphous polymers. Therefore, the present invention provides a porous hydrogen bond material for extracting uranium from seawater and a preparation method thereof. Summary of the invention
[0006] In order to solve the problem that the adsorption material in the above-mentioned prior art is an amorphous polymer, which may have unstable adsorption performance when extracting uranium from seawater due to the uncertain material structure, and it is difficult to effectively extract uranium directly from seawater, the present invention provides a porous hydrogen bond material for extracting uranium from seawater and a preparation method thereof.
[0007] The porous hydrogen-bonded material for extracting uranium from seawater and the preparation method thereof of the present invention are realized by the following technical scheme:
[0008] The first object of the present invention is to provide a method for preparing a porous hydrogen-bonded material for extracting uranium from seawater, comprising the following steps:
[0009] Step 1: In a solvent containing an inorganic base, a cyano compound and hydroxylamine hydrochloride are used as raw materials, and a heating and stirring reaction is performed to bond the nitrile group on the cyano compound with the hydroxylamine hydrochloride to obtain an amine oxime compound.
[0010] It should be noted that the present invention takes into account the presence of hydrochloric acid components in hydroxylamine hydrochloride. If the cyano compound and hydroxylamine hydrochloride are directly reacted, there may be a situation where hydroxylamine is not easily released, resulting in a situation where the reaction is slow or difficult to occur. Therefore, the present invention is preferably reacted in an alkaline solvent to provide an alkaline environment through the inorganic base component in the solvent, so as to achieve the purpose of neutralizing and releasing hydroxylamine with hydrochloric acid, so as to promote hydroxylamine to be bonded with the cyano group on the cyano compound, thereby promoting the formation of an amine oxime compound. The present invention does not limit the specific formation of the inorganic base in the alkaline solvent, as long as an alkaline environment can be provided, and hydroxylamine can be neutralized and released with hydrochloric acid. In some preferred embodiments of the present invention, the inorganic base used can be selected from any one or more of sodium hydroxide, sodium carbonate, potassium carbonate and cesium carbonate.
[0011] The preparation method of the present invention is suitable for small molecule cyano compounds to construct porous hydrogen-bonded materials, such as 4-nitrile phenyl compounds. In order to improve the adsorption effect of the porous hydrogen-bonded material obtained by the present invention on uranium, in some preferred embodiments of the present invention, the 4-nitrile phenyl compound used is any one of tetrakis(4-nitrile phenyl)ethylene, tetrakis(4-nitrile phenyl)methane and 1,3,5-tris(4-cyanophenyl)benzene, so that the porous hydrogen-bonded material formed by the 4-nitrile phenyl compound used as a building block has pores, which makes it easier for uranyl ions to enter the material, thereby achieving maximum adsorption of uranium.
[0012] In order to ensure that the cyano compound can fully react with hydroxylamine hydrochloride to form an amidoxime compound, in some preferred embodiments of the present invention, the molar ratio of the cyano compound, hydroxylamine hydrochloride and the inorganic base is 1:11-13:11-13.
[0013] In order to further ensure that the cyano compound can fully react with hydroxylamine hydrochloride to form an amidoxime compound, in some preferred embodiments of the present invention, the solvent used is one or both of methanol and ethanol, so that the cyano compound, hydroxylamine hydrochloride and sodium hydroxide have good solubility in the selected solvent, and then can fully react to form an intermediate product amidoxime compound. And in order to further ensure that the cyano compound, hydroxylamine hydrochloride and sodium hydroxide can be fully dispersed or dissolved in the selected solvent, in some preferred embodiments of the present invention, the amount ratio of the solvent to the cyano compound is 15mL to 25mL: 1mmol.
[0014] In order to ensure that the cyano compound can fully react with hydroxylamine hydrochloride to form an oxime compound during the heating and stirring process, the present invention has found in the process of exploration that the temperature of heating and stirring has an important influence on the oxime compound. When the temperature is too high, the cyano group is easy to become a carboxyl group, and the boiling point of the solvent is 65°C. Therefore, in some preferred embodiments of the present invention, the temperature of the heating and stirring reaction is 60°C to 70°C to ensure that the reaction can be completely converted into an oxime group. At the same time, the yield of the oxime compound can also be improved within this temperature range.
[0015] In order to ensure that the cyano compound can fully react with hydroxylamine hydrochloride to form an amidoxime compound at the above temperature, in some preferred embodiments of the present invention, the heating and stirring reaction time is 36h to 60h.
[0016] It can be understood that since the above-mentioned heating and stirring reaction is carried out in a solvent environment, the intermediate product oxime compound is still present in the solvent environment. Therefore, in some preferred embodiments of the present invention, the reaction liquid obtained by the heating and stirring reaction is also post-treated to obtain a pure oxime compound: after the reaction liquid obtained by the heating and stirring reaction is cooled to room temperature, water with a volume of 1.5 to 2 times the volume of the above-mentioned solvent is added to dilute and filter to obtain a precipitate, and then the precipitate is dried to obtain a pure oxime compound. The drying temperature is 95 to 105°C and the drying time is 24h to 48h.
[0017] Step 2, dissolving the amidoxime compound in an organic solvent to obtain a mixture; volatilizing the mixture at room temperature to obtain a porous hydrogen bond material for extracting uranium from seawater.
[0018] In order to obtain a crystal structure with regular pores, the present invention improves the adsorption effect of the material on uranyl ions, so the amidoxime compound obtained in step 1 is redissolved in an organic solvent to recrystallize it in the solvent, so that the molecules are rearranged into a crystal structure with pores, and a porous hydrogen bond material is obtained, thereby improving the adsorption of uranyl ions through regular pores. The present invention does not specifically limit the type of organic solvent used, as long as it can dissolve the amidoxime compound and realize its recrystallization. For example, the organic solvent used can be selected from one or more of methanol, isopropanol and tetrahydrofuran. Considering the cost and toxicity of the organic solvent, in some preferred embodiments of the present invention, the organic solvent used is preferably methanol. And in order to ensure that the organic solvent used can fully dissolve the amidoxime compound, in some preferred embodiments of the present invention, the amount ratio of the organic solvent used to the amidoxime compound is 80mL~120mL:50mg.
[0019] In order to avoid the presence of some tiny impurities in the compound, which may affect the quality of the crystal material, the present invention filters the mixture before volatilization to ensure that the impurities that may exist in the mixture are removed. In order to ensure that the above-mentioned effect can be achieved by filtering, in some preferred embodiments of the present invention, the filtration process uses a nano-membrane of 0.4μm to 0.5μm.
[0020] It should also be noted that, considering the diffusion arrangement rate of small molecules in the solvent and the volatilization rate of the solvent, in some preferred embodiments of the present invention, the volatilization time is 12 to 36 hours to ensure complete crystallization of the small molecules, thereby improving the yield.
[0021] The second object of the present invention is to provide a porous hydrogen bond material prepared by the above preparation method for extracting uranium from seawater.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The present invention uses a cyano compound as a raw material, reacts it with hydroxylamine hydrochloride to form an amidoxime compound, and then redissolves the compound and volatilizes it so that the amidoxime compound can be rearranged into a crystalline material with pores, thereby forming hydrogen bonds between N and OH in the amidoxime group and the amidoxime groups on adjacent molecules, and constructs a porous hydrogen-bonded material with a three-dimensional structure under the action of hydrogen bonds. The pores in the porous hydrogen-bonded material have comparable sizes, and there are groups in the pores that have specific adsorption to uranium ions, so uranium can be specifically adsorbed from seawater.
[0024] The preparation method of the present invention is simple and easy to industrialize. The porous hydrogen-bonded material prepared by the present invention has a three-dimensional structure with uniformly distributed pores, and can selectively adsorb uranium in seawater through the pore screening effect. The adsorption amount of U is about 50 times that of V, and the optimal pH range of the porous hydrogen-bonded material of the present invention is 7 to 8, which is more in line with the actual seawater pH = 8. And after testing, the porous hydrogen-bonded material of the present invention still maintains an adsorption amount of uranium at about 90% after 5 cycles. It shows that the porous hydrogen-bonded material of the present invention can be used to extract uranium from seawater.
[0025] The amide oxime material synthesized by the present invention is a small molecule and is easily dissolved by an organic solvent. Therefore, after the solvent evaporates, a single crystal formed by neatly arranged small molecules can be obtained. Compared with common COFs, fibers, or hyper-crosslinked compounds in the prior art, the porous hydrogen-bonded material of the present invention has a three-dimensional crystal structure with uniformly distributed pores, which can not only achieve selective adsorption of uranium in seawater, but also directly measure the structure, which is convenient for characterization without the need to use PXRD to infer the structure, which is helpful for subsequent further research on its adsorption mechanism. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 is the H of Tpe-AO prepared in Example 1 1 NMR spectrum.
[0027] Figure 2 is the H of Tpm-AO prepared in Example 2 1 NMR spectrum.
[0028] Figure 3 is the H of Tpb-AO prepared in Example 3 1 NMR spectrum.
[0029] Figure 4 This is the infrared spectrum of Tpe-AO prepared in Example 1.
[0030] Figure 5 This is the infrared spectrum of Tpm-AO prepared in Example 2.
[0031] Figure 6 This is the infrared spectrum of Tpb-AO prepared in Example 3.
[0032] Figure 7 This is the equilibrium adsorption isotherm test result of HOF-Tpe prepared in Example 1.
[0033] Figure 8 This is the equilibrium adsorption isotherm test result of HOF-Tpm prepared in Example 2.
[0034] Fig. 9This is the equilibrium adsorption isotherm test result of HOF-Tpb prepared in Example 3.
[0035] Fig.10 The adsorption results of uranium ions for HOF-Tpe prepared in Example 1, HOF-Tpm prepared in Example 2, and HOF-Tpb prepared in Example 3 at different pH values.
[0036] Fig.11 The kinetic adsorption test results of HOF-Tpe prepared in Example 1.
[0037] Fig.12 The kinetic adsorption test results of HOF-Tpm prepared in Example 2.
[0038] Fig.13 The kinetic adsorption test results of HOF-Tpb prepared in Example 3.
[0039] Fig.14 The test results of 5 cycles of adsorption-desorption of uranium captured by HOF-Tpe prepared in Example 1.
[0040] Fig.15 The test results of 5 cycles of adsorption-desorption of uranium captured by HOF-Tpm prepared in Example 2.
[0041] Fig.16 The test results of 5 cycles of adsorption-desorption of uranium captured by HOF-Tpb prepared in Example 3.
[0042] Fig.17 The selective adsorption results of HOF-Tpe prepared in Example 1 for different ions. DETAILED DESCRIPTION
[0043] The technical solutions in the embodiments of the present invention will be described clearly and completely below.
[0044] Example 1
[0045] This embodiment provides a porous hydrogen-bonded material for extracting uranium from seawater, and the porous hydrogen-bonded material is prepared by the following steps:
[0046] 1) Under atmospheric atmosphere, 1 mmol of tetrakis(4-nitrophenyl)ethylene, 12 mmol of hydroxylamine hydrochloride, 12 mmol of sodium hydroxide and 20 mL of methanol were mixed, and then stirred at 65° C. for 48 h. After cooling to room temperature, 30 mL of water was added and filtered to obtain a solid, which was dried at 100° C. for 36 h to obtain a light yellow solid, tetrakis(4-aminoximophenyl)ethylene, marked as Tpe-AO, with a mass of 500 mg and a yield of 88.6%.
[0047] And the reaction process of this step is shown in Reaction Formula 1:
[0048]
[0049] 2) According to the dosage ratio of 50 mg: 100 mL, the tetrakis(4-aminoximiphenyl)ethylene obtained above was added to the corresponding volume of methanol, and ultrasonicated for 10 minutes to completely dissolve the tetrakis(4-aminoximiphenyl)ethylene to obtain a mixed solution. The mixed solution was then filtered through a 0.45 μm nanomembrane into a headspace vial and evaporated at room temperature for 1 day to recrystallize the tetrakis(4-aminoximiphenyl)ethylene into a porous hydrogen-bonded material with a regular porous single crystal structure arrangement, labeled as HOF-Tpe.
[0050] Example 2
[0051] This embodiment provides a porous hydrogen-bonded material for extracting uranium from seawater, and the porous hydrogen-bonded material is prepared by the following steps:
[0052] 1) Under atmospheric atmosphere, 1 mmol of tetrakis(4-cyanophenyl)methane, 12 mmol of hydroxylamine hydrochloride, 12 mmol of sodium hydroxide and 20 mL of methanol were mixed, and then stirred at 65° C. for 48 h. After cooling to room temperature, 30 mL of water was added and filtered to obtain a solid, which was dried at 100° C. for 36 h to obtain a yellow-white solid, tetrakis(4-aminoximiphenyl)methane, marked as Tpm-AO, with a mass of 460 mg and a yield of 83.3%.
[0053] And the reaction process of this step is shown in Reaction Formula 2:
[0054]
[0055] 2) According to the dosage ratio of 50 mg: 100 mL, the tetrakis (4-aminoximiphenyl) methane obtained above was added to the corresponding volume of methanol, and ultrasonicated for 10 minutes to completely dissolve the tetrakis (4-aminoximiphenyl) methane to obtain a mixed solution. The mixed solution was then filtered through a 0.45 μm nanomembrane into a headspace vial and volatilized at room temperature for 1 day to recrystallize the tetrakis (4-aminoximiphenyl) methane into a porous hydrogen bond material with a regular porous single crystal structure arrangement, marked as HOF-Tpm.
[0056] Example 3
[0057] This embodiment provides a porous hydrogen-bonded material for extracting uranium from seawater, and the porous hydrogen-bonded material is prepared by the following steps:
[0058] 1) Under atmospheric atmosphere, 1 mmol of 1,3,5-tris(4-cyanophenyl)benzene, 12 mmol of hydroxylamine hydrochloride, 12 mmol of sodium hydroxide and 20 mL of methanol were mixed and then stirred at 65°C for 48 h. After cooling to room temperature, 30 mL of water was added and filtered to obtain a solid, which was dried at 100°C for 36 h to obtain a yellow-white solid, 1,3,5-tris(4-aminophenyl)benzene, marked as Tpb-AO, with a mass of 405 mg and a yield of 84.5%.
[0059] And the reaction process of this step is shown in Reaction Formula 2:
[0060]
[0061] 2) 50 mg of 1,3,5-tris(4-aminoximinophenyl)benzene was added to 100 mL of methanol and ultrasonicated for 10 minutes to dissolve the compound. The solution was filtered through a 0.45 μm nanomembrane into a headspace vial and evaporated at room temperature for 1 day to allow the crude product to recrystallize into a porous hydrogen-bonded material with a regular porous single crystal structure arrangement, labeled as HOF-Tpb.
[0062] Experimental Section
[0063] (1)H 1 NMR testing
[0064] The present invention takes Tpe-AO prepared in Example 1, Tpm-AO prepared in Example 2 and Tpb-AO prepared in Example 3 as examples, and H 1 NMR test, and the test results are as follows Figure 1-Figure 3 shown.
[0065] Figure 1 is the H of Tpe-AO prepared in Example 1 1 From the NMR spectrum, it can be seen that the present invention successfully synthesized Tpm-AO.
[0066] Figure 2 is the H of Tpm-AO prepared in Example 2 1 From the NMR spectrum, it can be seen that the present invention successfully synthesized Tpe-AO.
[0067] Figure 3 is the H of Tpb-AO prepared in Example 3 1 From the NMR spectrum, it can be seen that the present invention successfully synthesized Tpb-AO.
[0068] (2) Infrared spectrum test
[0069] The present invention takes Tpe-AO prepared in Example 1, Tpm-AO prepared in Example 2 and Tpb-AO prepared in Example 3 as examples, and infrared spectroscopy tests are performed on them respectively, and the test results are as follows: Figure 4-Figure 6 shown.
[0070] Figure 4 The infrared spectrum of Tpe-AO prepared in Example 1 shows that the amidoximation reaction is complete and the cyano groups have been completely converted into amidoxime groups.
[0071] Figure 5 This is the infrared spectrum of Tpm-AO prepared in Example 2. It can be seen that the amidoximation reaction is complete and the cyano groups have been completely converted into amidoxime groups.
[0072] Figure 6 The infrared spectrum of Tpb-AO prepared in Example 3 shows that the amidoximation reaction is complete and the cyano groups have been completely converted into amidoxime groups.
[0073] (3) Adsorption performance test
[0074] The present invention uses HOF-Tpe prepared in Example 1, HOF-Tpm prepared in Example 2, and HOF-Tpb prepared in Example 3 as absorbents, and conducts equilibrium adsorption isotherm experiments on them. The test results are as follows: Figure 7-Figure 9 shown.
[0075] Test method for equilibrium adsorption isotherm experiment:
[0076] At pH 7.0, U simulated solutions with initial concentrations of 5 mg / L, 8 mg / L, 10 mg / L, 12 mg / L, 15 mg / L and 18 mg / L were prepared. 100 mL of the above U simulated solutions with different concentrations were added with 1 mg of absorbent, stirred at room temperature for 36 h, and then aliquots were taken out and analyzed according to the arsenicazole III test.
[0077] Figure 7 The equilibrium adsorption isotherm test results of HOF-Tpe prepared in Example 1 show that the maximum adsorption capacity of uranium ions by HOF-Tpe at room temperature is 1200 mg·g -1 .
[0078] Figure 8 The equilibrium adsorption isotherm test results of HOF-Tpm prepared in Example 2 show that the maximum adsorption capacity of uranium ions by HOF-Tpm at room temperature is 490 mg·g -1 .
[0079] Fig. 9The equilibrium adsorption isotherm test results of HOF-Tpb prepared in Example 3 show that the maximum adsorption capacity of uranium ions by HOF-Tpb at room temperature is 1000 mg·g -1 .
[0080] By comparing the adsorption effects of the prior art with DOI No. 10.1002 / advs.201900002, the prior art with DOI No. 10.1016 / j.ijbiomac.2023.124792, the prior art with DOI No. 10.1016 / j.cej.2021.130060 and the prior art with DOI No. 10.1002 / adfm.201901009, it can be seen that the porous hydrogen bond materials of Examples 1 to 3 of the present invention generally have a higher adsorption capacity for uranium ions.
[0081] (4) Experiment on the effect of different pH on adsorption
[0082] The present invention uses HOF-Tpe prepared in Example 1, HOF-Tpm prepared in Example 2, and HOF-Tpb prepared in Example 3 as absorbents, and tests them in U simulated solutions with different pH values to determine their effects on the adsorption of uranium ions, and the test method is as follows:
[0083] The absorbent was added to 60 mL of a simulated U solution with a concentration of 10 ppm, and the pH of the solution was adjusted with hydrochloric acid or sodium hydroxide to 3, 4, 5, 6, 7, 8 and 9. After shaking with a magnetic stirrer at room temperature for 36 h, aliquots were separated and the concentration of residual uranium was analyzed by inductively coupled plasma optical emission spectrometry, i.e., ICP-OES, and the analysis results were as follows: Fig.10 shown.
[0084] Fig.10 From the adsorption results of uranium ions at different pH values for HOF-Tpe prepared in Example 1, HOF-Tpm prepared in Example 2 and HOF-Tpb prepared in Example 3, it can be seen that the HOF-Tpe prepared in Example 1, the HOF-Tpm prepared in Example 2 and the HOF-Tpb prepared in Example 3 all have the highest adsorption amount of uranium ions in the range of pH = 7 to 8, while the pH value of real seawater is 7 to 8, which indicates that the porous hydrogen bond materials of Examples 1 to 3 of the present invention can be used for uranium extraction in real seawater.
[0085] (5) Uranium capture kinetics experiment
[0086] The present invention uses HOF-Tpe prepared in Example 1, HOF-Tpm prepared in Example 2, and HOF-Tpb prepared in Example 3 as absorbents, and measures uranium capture kinetics at a concentration of 10 ppm at a pH value of 7.0, and the test method is:
[0087] Using 15ppm uranyl solution as simulated seawater, 2mg of absorbent was soaked and dispersed in 120mL of simulated seawater, and then stirred. When the stirring time was 5min, 10min, 20min, 60min, 240min, 360min, 540min, 720min, 900min and 1440min, 0.5mL of solution was taken out and centrifuged for detection, and the test results were sorted as follows: Figure 11-13 shown.
[0088] Fig.11 The kinetic adsorption test results of HOF-Tpe prepared in Example 1 show that the adsorption rate is fast and reaches equilibrium in about 700 min.
[0089] Fig.12 The kinetic adsorption test results of HOF-Tpm prepared in Example 2 show that the adsorption rate is fast and reaches equilibrium in about 600 min.
[0090] Fig.13 The kinetic adsorption test results of HOF-Tpb prepared in Example 3 show that the adsorption rate is fast and reaches equilibrium in about 300 min.
[0091] (6) Uranium adsorption-desorption cycle experiment
[0092] In order to evaluate the reusability of the porous hydrogen-bonded material prepared by the present invention, the present invention uses HOF-Tpe prepared in Example 1, HOF-Tpm prepared in Example 2, and HOF-Tpb prepared in Example 3 as absorbents to carry out uranium adsorption-desorption cycle experiments. The test method of the uranium adsorption-desorption cycle experiment is as follows:
[0093] Take 5 mg of absorbent and soak it in 300 mL of simulated seawater and stir it for 24 h. Then centrifuge and separate to obtain 200 mL of eluent. -1 Sodium carbonate and 0.1% hydrogen peroxide were used for regeneration until the concentration of the elution solution did not change as measured by ICP-OES. After the desorption process, the sample was further cleaned by soaking in 500 mL of deionized water and washing twice with circulating ultrapure water to completely remove the eluent for the next uranium capture. The above experimental steps were repeated 5 times in total, and the test results were organized as follows: Figure 14-16 shown.
[0094] Fig.14 The test results of 5 cycles of adsorption-desorption of uranium captured by HOF-Tpe prepared in Example 1 show that after five cycles, the adsorption amount has not decreased significantly and is still above 88%.
[0095] Fig.15 The test results of 5 cycles of adsorption-desorption of uranium captured by HOF-Tpm prepared in Example 2 show that after five cycles, the adsorption amount has not decreased significantly and is still above 88%.
[0096] Fig.16 The test results of 5 cycles of adsorption-desorption of uranium captured by HOF-Tpb prepared in Example 3 show that after five cycles, the adsorption amount has not decreased significantly and is still above 88%.
[0097] Depend on Figure 14-16 It can also be seen that the porous hydrogen-bonded material prepared by the present invention has good adsorption repeatability, and the adsorption rate can still reach more than 85% after 5 cycles, among which the adsorption rate of HOF-Tpe can reach more than 90% after five cycles.
[0098] (7) Selectivity experiments for different ions
[0099] The present invention takes into account that the above experiments all show that the porous hydrogen bond materials prepared in Examples 1 to 3 have good adsorption properties for uranium. Therefore, considering the factors of cost and research cycle, the present invention takes the HOF-Tpe prepared in Example 1 as an example to explore the selectivity of the HOF-Tpe prepared in Example 1 for different ions, and the test method is:
[0100] In order to accurately determine the affinity of the material for uranyl ions, 10 metal ions, namely Fe 3+ , VO4 3- 、Ni 2+ 、Zn 2 + 、Al 3+ , Pb 2+ 、Co 2+ , Cu 2+ Cr 3+ With uranyl ion UO2 2+ After the pH value of the mixed solution was adjusted to 7.0, 50 mg of HOF-Tpe prepared in Example 1 was immersed in 2 L of aqueous solution and shaken for 72 h, and then the residual uranium concentration in the solution was recorded and analyzed by inductively coupled plasma mass spectrometry. The analysis results are as follows: Fig.17 shown.
[0101] Fig.17 The selective adsorption results of HOF-Tpe prepared in Example 1 for different ions show that the adsorption amount of uranium ions by HOF-Tpe is much higher than that of other ions, and compared with vanadium, which is the closest to uranium ions and difficult to separate, the adsorption amount of uranium ions by HOF-Tpe is about 100% of that of VO4 3- 50 times the adsorption capacity.
[0102] Obviously, the above embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A method for preparing a porous hydrogen-bonded material for extracting uranium from seawater, characterized in that: The following steps are involved: In a solvent containing an inorganic base, a cyano compound and hydroxylamine hydrochloride are used as raw materials, and a heating and stirring reaction is performed to bond the nitrile group on the cyano compound with the hydroxylamine hydrochloride to obtain an amidoxime compound; The amidoxime compound is dissolved in an organic solvent to obtain a mixture; the mixture is volatilized at room temperature to allow the amidoxime compound to recrystallize into a single crystal compound with a regular porous structure, thereby obtaining a porous hydrogen-bonded material for extracting uranium from seawater.
2. The preparation method according to claim 1, characterized in that The cyano compound is a 4-nitrile phenyl compound.
3. The preparation method according to claim 2, characterized in that: The 4-nitrile phenyl compound is any one of tetrakis(4-nitrile phenyl)ethylene, tetrakis(4-nitrile phenyl)methane and 1,3,5-tris(4-cyanophenyl)benzene.
4. The preparation method according to claim 1, characterized in that: The molar ratio of the cyano compound, hydroxylamine hydrochloride and the inorganic base is 1:11-13:11-13.
5. The preparation method according to claim 1, characterized in that: The temperature of the heating and stirring reaction is 60° C. to 70° C., and the time is 36 h to 60 h.
6. The preparation method according to claim 1, characterized in that: Before volatilizing the mixture, filtering the mixture; The filtration process uses a nano-membrane of 0.4 μm to 0.5 μm.
7. The preparation method according to claim 1, characterized in that: The volatilization time is 12h to 36h.
8. The preparation method according to claim 1, characterized in that: The solvent is methanol; The usage ratio of the solvent to the cyano compound is 15 mL to 25 mL: 1 mmol.
9. The preparation method according to claim 1, characterized in that: The organic solvent is one or both of methanol and ethanol; The usage ratio of the organic solvent to the amine oxime compound is 80 mL to 120 mL: 50 mg.
10. A porous hydrogen-bonded material for extracting uranium from seawater prepared by the preparation method according to any one of claims 1 to 9.